First molecular identification of Australapatemon burti (Miller, 1923) (Trematoda: Digenea: Strigeidae) from an intermediate host Radix labiata (Rossmaessler) (Gastropoda: Lymnaeidae) in Europe - Aksenova, Olga V.; Bespalaya, Yulia V.; Bolotov, Ivan N.; Kondakov, Alexander V.; Sokolova, Svetlana E. (Zootaxa, 2016)
The strigeid digenean species Australapatemon burti (Miller, 1923) (Trematoda: Digenea: Strigeidae) was originally described from North America, but recorded in the Neotropical region (Drago et al. 2007; Hernández-Mena et al. 2014; Blasco-Costa et al. 2016) and in Central Europe (Faltýnková et al. 2007). In Europe, this species is rare, and there is not much information about its range (Faltýnková et al. 2007; Soldánová et al. 2012). Australapatemon burti has a complex life cycle with three larval stages, two of which (sporocyst and cercaria) use several species of freshwater snails, and the third stage (metacercaria) use non-specific host hirudineans (Dubois 1968; Davies & Ostrowski de Núñez 2012; Blasco-Costa et al. 2016). Adult flukes are parasitic in the intenstines of various waterfowl species, such as ducks and swans (Drago et al. 2007; Hernández-Mena et al. 2014). Currently, the molecular data on this parasite species includes only nucleotide sequences of four adult specimens from Mexico (Hernández-Mena et al. 2014). Their hosts were Mexican duck, Anas diazi Ridgway, American Wigeon, Anas americana Gmelin, Cinnamon Teal, Anas cyanoptera Vieillot, and Ruddy Duck, Oxyura jamaicensis (Gmelin) (Anserformes: Anatidae).